FMK-8 REGULATING FINANCE TO PROMOTE GROWTH: THE QUEBEC EXPERIENCE IN PERSPECTIVE - Pierre Lortie (The School of Public Policy Publications, 2023)
Canada has one of the largest and most developed financial systems in the world.  At the end of 2018, total assets of financial institutions reached 626 percent of GDP, placing Canada ahead of Japan, France, the United States and Germany on this metric, and the amount of debt securities outstanding and market capitalization amounted to 252 percent of GDP (IMF, 2019).